The professionalization of university teacher: Notes regarding the implementation of corporate strategies in college - Taymi Breijo Worosz; María De los Ángeles Novo; María Eugenia Bedoya Toro (Revista MENDIVE, 2014)
The professionalization o f the university professor, is considered one of the great challenges of higher education and is the basis for the solution of other major problems with the current University. The effective strategic direction of this process at the institutional level an d harmonious relationship with the evaluation of the University, is the scientific problem that this article suggests its theoretical results contribute to their solution.